Mental Health Outcomes Across the Lifespan in Individuals With Persistent Post-Concussion Symptoms: A Scoping Review - Sheldrake, Elena; Al-Hakeem, Hiba; Lam, Brendan; Goldstein, Benjamin I.; Wheeler, Anne L.; Burke, Matthew; Dunkley, Benjamin T.; Reed, Nick; Scratch, Shannon E. (Frontiers in Neurology, 2022)
Objective: Concussion is a common yet heterogenous injury. Approximately 15–30% of cases present with persistent post-concussion symptoms (PPCS), continuing 4 weeks or more post-injury in children, youth, and adolescents, and 3 months or more in adults. There are known bidirectional links between PPCS and mental health outcomes. The focus of this scoping review is to explore the literature on mental health outcomes in individuals experiencing PPCS. Research objectives were to explore: (1) the mental health outcomes of individuals with PPCS and types of assessments used to identify mental health outcomes this group, and (2) how mental health outcomes compare in terms of similarities and differences among pediatric and adult populations with PPCS. Method Ovid MEDLINE; EMBASE; CINAHL, and PsycInfo databases were searched. After title and abstract screening of 11,920 studies, 481 articles were reviewed. Twenty-five papers met inclusion criteria. Results were organized by mental health outcomes of pediatric and adult populations, separately. Results There was a significantly higher number of studies devoted to adult populations. Of the 25 studies, 19 (76%) focused on adults, while six (24%) focused on adolescents. In adult populations, studies focused on symptoms of: anxiety (n = 2), depression (n = 8), and anxiety and depression (n = 9). Two studies assessed other emotional outcomes (10.5%). Within pediatric populations, an equal number of studies explored symptoms of: anxiety (n = 2), depression (n = 2), and anxiety and depression (n = 2). No studies focused on other emotional outcomes. Studies ranged greatly in methods, design, and control group. Most studies reported higher psychiatric symptoms of anxiety and/or depression in those with PPCS compared to individuals with recovered concussion or healthy controls. Discussion This review contributes to the understanding of mental health outcomes in those experiencing PPCS. Mental health and PPCS requires greater attention in pediatric populations, and consider strategies for those experiencing PPCS and mental health impacts. Future studies should consider including a wider range of emotional outcomes in their design, not limited to anxiety and depression. Study results may lead to improvements and research in the identification, assessment, and management of PPCS and mental health.